Warning signage on cigarette packaging and buying behavior: Does it really matter? - Lau, Wee Ming; De Run, Ernest Cyril; Ting, Hiram; Chuah, Chin Wei; Singh, Gursimran (2016)
The implementation of warning signage on cigarette packaging is widely practiced in various parts of the world, including developing markets.The purpose is to discourage people from buying cigarette and smoking.Despite the effort to promote the importance of health to the public's, the effectiveness of warning signage with negative messages on cigarette packaging remains largely inconclusive.Hence, the present study attempts to investigate the effect of religiosity, cultural orientation and peer influence on buying cigarette, and the moderation effect of warning signage on cigarette packaging in the Sarawakian context.Utilizing purposive sampling technique, self-administered questionnaire was administered. 156 usable copies were collected in a month time. Data were then analyzed using PROCESS macro in SPSS. The findings show that while peer influence has positive effect on buying behavior, warning signage only moderates the relationship between cultural orientation and buying behavior. As such it highlights the importance to cultivate healthy cultural values, and suggests the need to utilize warning signage on packaging in the appropriate manner so as to communicate the intended messages effectively.Implications and future studies are provided.